Marine algal virus communities along Southern African coasts - Morrissey, Kathryn Lee (Department of Biological Sciences, 2016)
Southern Africa is home to highly diverse marine environments along its coasts. The main reason for the contrasting environments is the two major boundary currents, the Benguela and Agulhas currents, and their interaction around the tip of South Africa. Algal blooms are known to proliferate predominantly off the nutrient - rich west coast, however, sporadic inshore upwelling on the east coast can also illicit these events. In addition, solar salt - pans located on the coast that draw their water from the bay area are affected by bloom events. Algal viruses play a key role in regulating phytoplankton communities and modulate the dynamics of these bloom events. Identifying the viruses associated with algal blooms is the first step in determining the role they play in the bloom dynamics. Here I chose to focus on phycodnaviruses, known agents of bloom termination. Samples were taken from two specific algal blooms that occurred in 2013 in different bioregions namely Elands Bay (west coast) and Algoa Bay (east coast). Additionally the Cerebos solar salt pans located along the west coast were selected as sample sites to investigate viral composition. DNA polymerase (pol) gene fragments were amplified from environmental samples using algal - virus specific PCR primers AVS1 and POL. Amplified fragments were then sequenced. Viral sequences were identified and mapped to existing virus families. Amplicon specific primers were designed for select dominant virus group identified for both bloom events. These were used to screen across all samples to determine viral prevalence. Phylogenetic analysis of viral sequences revealed new clades of Phycodnaviridae in the Elands Bay and Algoa Bay regions. A bloom terminating virus, EB1, is proposed for the Elands Bay bloom event. The Cerebos salt pans showed the greatest diversity of all samples analysed and novel halophilic algal viruses were identified in regions with the highest salinity.